Pengaruh Kualitas Audit, Kondisi Keuangan, Dan Manajemen Laba Terhadap Opini Audit Going Concern - Almira Siva Devina Wijanarko; Anastasya Simanjuntak; Ellisa Noviana Dera; Rizkya Sukma Putri; Niketri Mustika Angela; Herlina Manurung (Pusat Riset dan Inovasi Nasional, 2024)
The company can be said to successfully run its business influenced by environmental factors to maintain its business until the future. The purpose of this study is to understand (1) factors that can influence the going concern audit opinion (2) strategies in handling the situation appropriately in receiving the going concern audit opinion assessment (3) the impact of the going concern opinion on the company's reputation. This research method is a literature review approach, a data collection technique from several previous studies that can then be concluded. The study’s results and analysis are (1) audit quality does not affect the going concern audit opinion because each auditor must be independent in carrying out their duties and the opinions given have the same standard procedures. However, another opinion states that audit quality affects the going concern audit opinion because large public accountants show the level of sustainability of the company more accurately than small public accountants. (2) Financial condition affects the going concern statement because if the financial condition is bad, the entity will find it difficult to maintain its business continuity. In addition, it was also found that financial condition did not affect the going concern statement due to poor financial condition due to the implementation of sustainable business operations through planning. (3) Profit management does not influence the going concern audit opinion because the auditor does not see the continuity of results but is oriented towards the situation of the entire company.